Resilience (hbr emotional intelligence series) - Goleman, Daniel, (HBR emotional intelligence series., 2017)
How do some people bounce back with strength from daily setbacks, professional crises, or intense trauma? This book will help you train your brain to withstand the pace of daily life, reveal the key traits of those who emerge stronger from challenges, and present an approach to an effective career reboot. This volume includes the work of: - Daniel Goleman - Jeffrey A. Sonnenfeld - Shawn Achor--